Workforce Diversity and Productivity of Organization: A Case of Nepalese Commercial Banks - Sethi, Royal (Nepalese Journal of Management, 2024)
This study examines the workforce diversity and productivity of organization: A case of Nepalese commercial banks. Job satisfaction is the dependent variable. The selected independent variables are age diversity, gender diversity, race and ethnicity diversity, education diversity, culture diversity, and physical and mental abilities diversity. The primary source of data is used to assess the opinions of respondents regarding age diversity, gender diversity, race and ethnicity diversity, education diversity, culture diversity and physical and mental abilities diversity towards workforce diversity and productivity of organization. The study is based on primary data of 151 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of workforce diversity and productivity of organization: A case of Nepalese commercial banks.The study showed that age diversity is positively correlated to job satisfaction. It indicates that organization having employee from different age group leads to increase in the satisfaction of employee’s satisfaction towards their job. Likewise, gender diversity is positively correlated to job satisfaction. It indicates that equality in gender diversity leads to increase in productivity and job satisfaction of employee. Similarly, race and ethnicity diversity is positively correlated to job satisfaction. It indicates that firm having employee from different racial and ethnic background leads to increase in job satisfaction of employee. Moreover, educational diversity is positively correlated to job satisfaction. It implies that employee from different educational background leads to increase in job satisfaction. Further, cultural diversity is also positively correlated to job satisfaction. It implies that drawing employee from a diverse culture leads to increase in job satisfaction of an employee. Moreover, physical and mental abilities diversity is positively correlated to job satisfaction. It indicates that firm having diversity of physical and mental abilities in an organization have numerous benefits to organization that leads to increase in job satisfaction.